The Project STARS (Strategic Action Towards Radiant Students): Empowering ABM Students Amidst Pandemic - Glenda V. Lumanta (Newinera Publisher, 2021)
This study sought to empower ABM students of Canda NHS which covered from January - June 2021 with the use of different plaforms such as messenger, google and limited face to face. This qualitative study utilized a descriptive-evaluative design. A research population of thirteen (13) and twenty-eight (28) with the total of forty-one (41) served as the respondents. Findings of the study revealed that the Project STARS (Strategic Action towards Radiant Students) is a great help project to empower students amidst pandemic. The ten (10) activities strategic action plan of the project must be consistently conduct yearly because it increase awareness, leadership as well as empowering students. With different programs and activities of the project, ABM students are able to lead, make decision, preparation of assigned functions and organize activities. No signal or internet connection and lack of budget are some of the major problems why only 80% attained participation of ABM students and all activities of the project via different online plaforms are very important and need to add Bookkeeping webinar. Further, the researcher recommended that Project STARS (Strategic Action towards Radiant Students) must be consistently doing yearly, enhance activities, and strengthening partnership and make school wide with the different programs such as capacity development program, barkada kontra droga program and solid waste management program since it had a great impact to ABM students.